Geographic Information System Fire Disaster Mapping in Samarinda City Web-Based - Muh. Ibnu Fajar; Ida Maratul Khamidah; F. V. Astrolabe Sian Prasetya (Journal of Geomatics Engineering, Technology, and Science, 2022)
One of the problems that are often faced by the fire department at the time of a fire is the obstruction of the main post in determining the PMK assistance post which is deployed in the closest radius to the location of the incident. The purpose of this research is to build a web-based geographic information system that can determine and provide information about the location of fires in Samarinda City. The benefits of this geographic information system for mapping fire disasters can determine and become a source of information for the community and also the Fire Department regarding the location of the fire.